Інтелектуальна біографія Павла Полуботка: обстоювання традиції «модернізаційною» риторикою (до 350-річчя Павла Полуботка) - Кононенко, В.П. (Український історичний журнал, 2010)
Статтю присвячено недостатньо дослідженому аспекту модернізації
суспільно-політичної свідомості на периферії європейської цивілізації та
ранньокапіталістичної економіки, що розглядається крізь призму інтелектуальної біографії українського наказного гетьмана П.Полуботка. Висвітлюються його спроби підлаштувати традиційне суспільно-політичне
життя Гетьманщини під нові умови модернізованої Петром І Московської держави/Російської імперії. The paper is dedicated to insufficiently aspect of modernization of political
consciences on South-Eastern border of European civilization and periphery
of Early Modern capital economy. P.Polubotok’s intellectual biography is
presented and discussed in the research. Ukrainian nakaznyi hetman considered
as representative of Cossack intellectuals of Hetmanate. Secular intellectuals
of Hetmanate were social group which were consisted of well-educated
representatives of Cossack officers, Znachne military society and military clerks.
It is indicated that the main factor of evolution of social-political imaginations
and ideas of Cossack intellectuals of Hetmanate (and P.Polubotok too) became
modernization of Central-European societies. It is stated that modernization
consisted in transformation of traditional society into modern one that was
based on ideas of the «common wealth», «well-ordered state», clear laws, and
practices of their realization. It is indicated that P.Polubotok and his entourage
defended traditional social-political Cossack autonomy (old freedoms) by modern
terminology (novelties).